2017
DOI: 10.1016/j.rmed.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Serum surfactant protein D predicts the outcome of patients with idiopathic pulmonary fibrosis treated with pirfenidone

Abstract: The serum SP-D level was a predictor of disease progression and prognosis in patients with IPF treated with pirfenidone. In addition, this analysis describes the relative usefulness of other clinical parameters at baseline in estimating the prognosis of patients with IPF who are candidates for pirfenidone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…On the other hand, our study indicated the changes in serum levels of SP-A and KL-6 correlated signi cantly with changes in respiratory function, which re ects disease activity. These results are also consistent with other reports [6,10,11,26,28,32,33,[35][36][37][38]. Because of the di culty of respiratory function tests for patients of ILD, this evidence strongly supports the value of biomarkers in monitoring the activity of ILDs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, our study indicated the changes in serum levels of SP-A and KL-6 correlated signi cantly with changes in respiratory function, which re ects disease activity. These results are also consistent with other reports [6,10,11,26,28,32,33,[35][36][37][38]. Because of the di culty of respiratory function tests for patients of ILD, this evidence strongly supports the value of biomarkers in monitoring the activity of ILDs.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, pretreatment serum levels of SP-A and KL-6 did not relate to disease prognosis. It was reported that pretreatment KL-6 levels was signi cantly different depending on the response of pirfenidone therapy for IPF [32]. In the present study, pirfenidone was used on only 6 patients; the difference of treatment may affect this discrepancy.…”
Section: Discussionmentioning
confidence: 68%
“…The daily dose of pirfenidone was increased in a stepwise manner from 600 mg to 1200-1800 mg every 2 weeks, as previously described [15]. The median maximum dose was 1500 mg (inter-quartile range [IQR], 1200-1800 mg), and the median final dose was 1200 mg (IQR, 1200-1800 mg).…”
Section: Pirfenidone and Nintedanib Treatmentmentioning
confidence: 99%
“…13 In fact, it is reported that serum SP-D levels may predict the effectiveness of antifibrotic therapy. 14 In this study, a potent antifibrotic efficacy by RTX may be indicated as rapid decrease of SP-D in the good responder group. Meanwhile, baseline SP-D levels did not correlate with %FVC.…”
Section: Discussionmentioning
confidence: 88%